Reconstructing the phylogeny of the hornless rhinoceros Aceratheriinae - Lu, Xiao-Kang; Deng, Tao; Pandolfi, Luca (Frontiers in Ecology and Evolution, 2023)
This study presents the first phylogenetic analysis focused on the Subfamily Aceratheriinae to date, with 392 characters coded from 50 taxa at the species level. We added 80 newly defined and 33 revised characteristics, including features of the skull, teeth, and postcranial bones. Based on result of cladistic analysis, combined with diagnosis of traditional morphological taxonomy, we revised the diagnosis of Aceratheriinae and reconstructed the phylogeny of Aceratheriinae. In the present analysis, the tribe Teleoceratini, as well as the tribe Aceratheriini, was reclassified within Aceratheriinae, however, the traditionally established monophyly of each tribe was decomposed. The Aceratheriinae has undergone evolutionary adaptation several times during the early stage of evolution, and several genera have been reconstructed as early diverging taxa, such as Floridaceras, Galushaceras, Chilotheridium, Plesiaceratherium and Dromoceratherium; Diaceratherium, Aprotodon and Mesaceratherium from the Late Oligocene to the Early Miocene were united as the earliest divergent clade of Aceratheriinae. Alicornops was reclassified as member of Teleoceratini. Aceratheriini and Teleoceratini have been redefined as two highly specialized groups of Aceratheriinae. Furthermore, Aceratheriini shows two different adaptations in aspects of the skull outlines and the occlusal patterns of the cheek teeth. Turkanatherium, Molassitherium, and Protaceratherium are precluded from Aceratheriinae in this study, their phylogenetic positions remain debatable.